FROM PREPAREDNESS TO RESILIENCE: A QUALITATIVE-META-SYNTHESIS ON INTEGRATING GOVERNANCE, MEDIA, AND GEO-SPATIAL TECHNOLOGIES FOR EFFECTIVE DISASTER RISK REDUCTION IN PAKISTAN - Alina Ishrak; Nisfariza Binti Mohd Noor; Sumera Batool; Aimee Binti Halim; Safiah Yusmah Binti Muhammad Yusoff, (Malaysian Journal of Tropical Geography (MJTG), 2025)
Floods remain one of the most devastating and recurring climate-induced disasters in Pakistan, exposing the pervasive nature of risks alongside communication, technological, and governance challenges. This study explores how combining risk-informed governance, media, and geospatial technologies can strengthen resilience in flood-prone areas across the country. Using qualitative meta-analysis, it examines institutional frameworks, and the roles of geoscience and media, in shaping disaster preparedness, response, and long-term resilience with reference to the Sendai Framework. It highlights how geospatial technology supports the entire cycle from preparedness to resilience, while media plays a critical role in effective mobilization, communication, and awareness. The discussion situates floods within broader debates on risk knowledge, disaster risk governance, policy implementation mechanisms, fiscal policies for disaster risk reduction, and post-disaster “Build Back Better” initiatives. It emphasizes the importance of both technological and policy evolutions in mitigating escalating flood risks. Case studies of flood events, specifically the 2010 and 2022 floods in Pakistan, highlight uneven access to communication infrastructure, a lack of risk knowledge among communities, and limited capacity-building initiatives for both geospatial and media technologies, challenges that are deepened by existing socio-economic inequalities. By bridging perspectives from geography and media studies, the study argues that the effective integration of risk governance and modern technologies is essential for reducing vulnerabilities. The analysis offers policy frameworks to institutionalize geospatial technologies, strengthen governance mechanisms, and expand digital media infrastructure, all of which are critical to advancing inclusive and optimal flood resilience in Pakistan.